Population genetics of 24 Y‐STR loci in Chinese Han population from Jilin Province, Northeast China - Xu, Xiao‐ming (Mol Genet Genomic Med, 2019)
BACKGROUND: It is meaningful to expand the available population information on forensic medicine and to investigate the genetic characteristics of Han population from Jilin Province, Northeast China. METHODS: In this study, we investigated the genetic characteristics of 24 Y‐chromosomal short tandem repeat (STR) loci in 1,088 unrelated Chinese Han male individuals from Jilin Province, using DNATyper(TM) Y24 amplification kit. Additionally, we performed the population comparison between the Jilin population and the other nine reported populations based on the Y‐STR genotyping haplotypes. RESULTS: A total of 1,067 different haplotypes were found from 1,088 unrelated individuals, of which 1,046 were unique and 21 were shared by two individuals. The gene diversity values of 22 loci ranged from 0.3870 (DYS391) to 0.9668 (DYS385ab). The random match probability was 0.0010 with the discrimination capacity of 0.9807. Population comparison showed that there were minor differences compared to Beijing Chinese Han, China Manchu, Gansu Chinese Han, and Jiangsu Chinese Han, but major differences with respect to the populations of Guangdong Chinese Han, Yunnan Chinese Han, China Hui, China Korean, and China Tibetan. CONCLUSION: Our results showed that the 24 Y‐STR loci in Jilin Han population are valuable for forensic application and human genetics.